Enhanced Early Innate and T Cell-mediated Responses in Subjects Immunized with Anthrax Vaccine Adsorbed Plus CPG 7909 (AV7909) - Minang, Jacob T. (2014)
NuThrax(™) (Anthrax Vaccine Adsorbed with CPG 7909 Adjuvant) (AV7909) is in development. Samples obtained in a Phase Ib clinical trial were tested to confirm biomarkers of innate immunity and evaluate effects of CPG 7909 (PF-03512676) on adaptive immunity. Subjects received two intramuscular doses of commercial BioThrax(®) (Anthrax Vaccine Adsorbed, AVA), or two intramuscular doses of one of four formulations of AV7909. IP-10, IL-6, and C-reactive protein (CRP) levels were elevated 24 to 48 hours after administration of AV7909 formulations, returning to baseline by Day 7. AVA (no CPG 7909) resulted in elevated IL-6 and CRP, but not IP-10. Another marker of CpG, transiently decreased absolute lymphocyte counts (ALC), correlated with transiently increased IP-10. Cellular recall responses to anthrax Protective Antigen (PA) or PA peptides were assessed by IFN-gamma ELISpot assay performed on cryopreserved PBMCs obtained from subjects prior to immunization and 7 days following the second immunization (study day 21). One-half of subjects that received AV7909 with low-dose (0.25 mg/dose) CPG 7909 possessed positive Day 21 T cell responses to PA. In contrast, positive T cell responses occurred at an 11% average rate (1/9) for AVA-treated subjects. Differences in cellular responses due to dose level of CPG 7909 were not associated with differences in humoral anti-PA IgG responses, which were elevated for recipients of AV7909 compared to recipients of AVA. Serum markers at 24 or 48 hours (i.e. % ALC decrease, or increase in IL-6, IP-10, or CRP) correlated with the humoral (antibody) responses 1 month later, but did not correlate with cellular ELISpot responses. In summary, biomarkers of early responses to CPG 7909 were confirmed, and adding a CpG adjuvant to a vaccine administered twice resulted in increased T cell effects relative to vaccine alone. Changes in early biomarkers correlated with subsequent adaptive humoral immunity but not cellular immunity.